Kesia-Siaan Eksistensi: Makna Kehidupan Menurut Pesimisme Klasik AbÅ« al-Ê»AlÄ al-MaÊ»arrÄ«: Extistential Nihilism: The Meaning of Life According to the Classical Pessimism of AbÅ« al-Ê»AlÄ al-MaÊ»arrÄ« - Moh. Ariful Anam (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
This article discusses the thought of the classical pessimist philosopher in the Islamic world, it is known as AbÅ« al-Ê»AlÄ al-MaÊ»arrÄ« (363-449 H/973-1058 AD). The main topic studied is the biography of al-Ma'arrÄ« and his thoughts on the meaning of human existence in this world. To exhume the data, the researcher used the works of the classical encyclopedia to reconstruct the biography of al-MaÊ»arrÄ« and one of his monumental works, Al-LuzÅ«miyyÄt, to examine his thinking. This literature research uses historical analysis methods and content analysis. The results of this study are, first, the background of al-Ma'arrÄ«'s life, which is born from a respected family with his physical condition as a blind person who forms a different person from al-Ma'arrÄ« although he still obtained a fairly decent life. As well as the intellectual odyssey and the social conditions in which he interacted greatly influenced al-Ma'arrÄ«'s thought, making himself not complain about himself, instead reflecting it into philosophical ideas. Second, al-Ma'arrÄ«'s pessimism in interpreting human existence as futility (the vanity of existence). Human beings have been overwhelmed with evil potential from the beginning. So that his life is also full of suffering. There is nothing happier than death. Death is a great achievement and peace. While born in this world is a misfortune, suffering, and evil. In this context al-Ma'arrÄ« has a view that humans should not need to have children (childfree). Â Keywords :Â  al-Maâ€˜arrÄ«, pessimism, the vanity of existence